25S=52+54+56+.............+52002
25S-S=52002-1
24S=52002-1
S=\(\frac{5^{2002}-1}{24}\)
Ta có: S=1+52+54+56+...+52000
=>5S=5+53+55+57+...+52005
=>5S-S=4S=52005-1
=>S=\(\frac{5^{2005}-1}{4}\)
Vậy S=\(\frac{5^{2005}-1}{4}\)
Ta có: S=1+52+54+56+...+52000
=>5S=5+53+55+57+...+52005
=>5S-S=4S=52005-1
=>S=\(\frac{5^{2005}-1}{4}\)
S = 1 + 52 + 54 + 56 + .... + 52000
Nhân 52 vào vế S , ta được :
25S = 52.( 1 + 52 + 54 + 56 + .... + 52000 )
⇒ 25S = 52 + 54 + 56 + 58 + .... + 52002
Lấy biểu thức 25S - S , ta được :
25S - S = ( 52 + 54 + 56 + 58 + .... + 52002 ) - ( 1 + 52 + 54 + 56 + .... + 52000 )
⇒ 24S = 52002 - 1
⇒ S = ( 52002 - 1 ) : 2